Roles of Wnt3a and Dkk1 in experimental periodontitis - Jianqi Liu; Xiaobin Ren; Mingzhu Zhang; Yayan Lei; Yuhua Chen; Hongbing He (Elsevier, 2017)
Background/purpose: Periodontitis is an inflammatory, destructive disease caused by periodontal bacteria, and its molecular mechanism remains unclear. The aims of this study are to evaluate the expressions of Wnt3a and Dkk1 in experimental periodontitis (EP) and preliminarily explore their roles in periodontal diseases. Materials and methods: A total of 64 six-week-old male Sprague-Dawley rats were randomly divided into a normal group and an EP group. The EP group was prepared by using silk ligature combined with intraoral bacteria inoculation. To assess the periodontal inflammation and bone destruction extent, hematoxylin and eosin staining and tartrate-resistant acid phosphatase staining was performed 2 weeks, 4 weeks, and 6 weeks after the modeling, respectively, and immunohistochemistry and enzyme-linked immunosorbent assay were also performed to detect the changes of Wnt3a and Dkk1 in periodontal tissue and plasma. Results: Wnt3a expression was significantly decreased in the EP group when compared with the normal group (P < 0.05). Meanwhile, Dkk1 expression was significantly increased in the EP group when compared with the normal group (P < 0.05). Conclusion: The expression of Wnt3a and Dkk1 was well correlated with EP. It is suggested that Wnt3a and Dkk1 may be involved in periodontal diseases. Keywords: Dkk1, osteoblasts, periodontitis, Wnt3a